Arquitetura portuguesa: da Escola do Porto à Escola do Siza - Duarte, Yuri de Souza (2019)
The production of the modernist movement in Portugal took place in singular path of a resistance posture to models pre-conceived. Well-know Porto’s School and recognized from the decade of 1950, was a movement that produced echoes identified on the architectural productions up to the Portuguese until the present time. Among other characteristics, it shows harmony as a requeriment of project between the plot of the building and the surrounding pré-existent, providing better quality of use, comfort and esthetic beauty of the space in the city. Focused in the Portuguese architecture, the study starts from the contribution of the main exponents of the movement: Fernando Távora, Álvaro Siza Vieira and Eduardo Souto de Moura, which, in his work, ally the innovations of the modernist movement with the respected necessity to the traditions of the town, his materiality and the context of the new constructions regarding the urbane city préexistent. So, there will be presented the historical trajectory of the roots of the contemporary architecture in Portugal, from the decade of 1930, with the analysis of the intellectual production and projetual of the architects Carlos Ramos and Fernando Távora, up to the present. Next, a group of contemporary architects will be presented, composed for: John Carrilho da Graça; the brothers Manuel and Francisco Nuno Aires Mateus; the brothers Nuno and José Mateus (office ARX); and Nuno Brandão Costa, whom shows echoes of this trajectory in his production, for analysis of aspects of his formation and professional trajectory, like professional experience and architectural language adopted in his works. Then, this study will make a appreciation of contemporary buildings, located in Portugal and conceived by this group, above several aspects, such as: his insertion in the city, ways of use and his process of conception. For that, it will be necessary to understand different aspects of this space, how it will identify in which form the adjacent public space to iconic’s buildings contributes to give distinction or order that pré-existent minimizes the visual impact of the construction before those elements, considering still the necessity of looking, in the speech of the authors of the works, how was the concern about the space around the building on the context in the process of the project as a whole piece. Lastly, this study aims to contributes to the analysis of the quality of the public’s projects connected to contemporary buildings in the cities, for to the production of a cohesive urbanity.